Kewajiban Sertifikat Halal Untuk Produk Impor di Indonesia - Syafrida, Syafrida; Hartati, Ralang (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
AbstractGlobalization and free trade cause increased circulation of products both imported and local in the community. The Republic of Indonesia as the country with the largest Muslim population in the world. Islamic Sharia requires its people to consume halal products and forbid products that are not halal. Article 4 UUJPH, all products circulating in the community must be halal certified. Many imported food and beverage products traded in the community have not provided protection and guaranteed halal products for Muslim consumers. The problem is, how is the halal certificate procedure for imported products in force in Indonesia. The research method used is library research using secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials, normative juridical research. The result of the research is that imported products that are certified overseas that have cooperated with the adjustment of halal certificates with the State of Indonesia, then imported products are no longer required to submit applications for halal certificates, but to register overseas halal certificates at BPJPH to obtain a halal registration number from the head of BPJPH. The halal registration number is listed next to the halal logo on the product packaging or in certain places that are easily seen, read by consumers.Keywords: Halal Certificate, Imported Products, UUJPHÂ AbstrakGlobalisasi dan perdagangan bebas menyebabkan meningkatnya peredaran arus produk baik impor maupun lokal di masyarakat. Negara Republik Indonesia sebagai Negara berpenduduk muslim yang terbesar di dunia. Syariat Islam mewajibkan kepada umatnya untuk mengonsumsi produk halal dan mengharamkan produk yang tidak halal.Â Pasal 4 UUJPH, semua produk yang beredar di masyarakat wajib bersertifikat halal. Banyak produk impor makanan dan minuman yang diperdagangkan di masyarakat yang belum memberikan perlindungan dan jaminan kehalalan produk bagi konsumen muslim. Â Permasalahan, bagaimana prosedur sertifikat halal untuk produk impor yang berlaku di Indonesia. Metode penelitian yang digunakan adalah penelitian kepustakaan dengan menggunakan data sekunder berupa bahan hukum primer, bahan hukum sekunder dan bahan hukum tertier, peneltian bersifat yuridis normatif. Hasil penelitian bahwa produk impor yang bersertifikat luar negeri yang telah melakukan kerja sama penyesuaian sertifikat halal dengan Negara Indonesia, maka produk impor tidak diperlukan lagi mengajukan permohonan sertifikat halal, tetapi melakukan registrasi sertifikat halal luar negeri pada BPJPH untuk mendapatkan nomor registrasi halal dari kepala BPJPH. Nomor registrasi halal tersebut dicantumkan berdekatan dengan logo halal pada kemasan produk atau pada tempat tertentu yang mudah dilihat, dibaca oleh konsumen.Kata Kunci: Sertifikat Halal, Produk Impor, UUJPH